Customer satisfaction in ai-enabled banking: the roles of preferred banking mode and digital literacy - Syed Salman; Dr. Chaya R (Journal of Corporate Finance Management and Banking System, 2026)
The speedy adoption and integration of Artificial Intelligence (AI) in banking operations and services through platforms like chatbots, mobile banking, and intelligent ATMs have extensively revolutionized customer interactions and banking operations. Although current literature explores the efficiency and customization advantages of Artificial Intelligence in banking operations and services, few studies investigate the main and interaction effects of customer satisfaction through preferred banking mode and digital literacy, especially in developing countries such as India. Focusing on this research gap, the study analyzes the main and interaction effects of Preferred Banking Mode (digital, hybrid, and traditional) and Digital Literacy (low, moderate, and high) on customer satisfaction in the context of AI-enabled banking services. A quantitative, cross-sectional research approach is adopted using a structured questionnaire administered to 390 banking customers in Bangalore. Customer satisfaction is measured using a reliable multi-item Likert scale (alpha = 0.915), and data is analyzed using two-way ANOVA. The results reveal significant main and interaction effects, with higher satisfaction among digitally literate customers using digital banking.